15-minute consultation: A structured approach to the assessment of chest pain in a child. Issue 4 (3rd December 2013) - Collins, Samuel A; Griksaitis, Michael J; Legg, Julian P
Abstract : This article aims to provide a concise, structured approach to the child with chest pain. Chest pain is a common presenting symptom in children but, unlike in adults, the cause is rarely cardiac. We review the main causes of chest pain in children and discuss the important features that may alert those assessing paediatric chest pain to serious underlying pathology. In the vast majority of cases, reassurance is all that is required and a thorough initial consultation can exclude rare, serious disease and provide vital reassurance to children and families.